2013
DOI: 10.1080/10158782.2013.11441526
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pulmonary tuberculosis outcomes among inmates in Potchefstroom Prison in North West province

Abstract: View related articles 2013;28(2) South Afr J Epidemiol Infect Original Research: Factors associated with pulmonary tuberculosis outcomes among inmates in Potchefstroom Prison Tuberculosis is the leading cause of death among the world's prison populations. Prisons are reservoirs of tuberculosis and threaten inmates, prison staff, visitors and the surrounding community. This study was carried out to explore the associated factors with pulmonary tuberculosis treatment outcomes at Potchefstroom Prison. A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
6
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 7 publications
7
36
6
5
Order By: Relevance
“…Amongst TB cases, prevalence of HIV positivity varied from 0.1% [47] to 73.1% [49]. There were few clear geographical patterns within the results; studies performed in African countries often reported co-infection prevalence over 50% in TB cases [49,60,61,68]. As with measures of incidence, this wide variation in prevalence estimates may be in part due to the settings and characteristics of the prisoners themselves but also in part to methodological differences in calculation of prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst TB cases, prevalence of HIV positivity varied from 0.1% [47] to 73.1% [49]. There were few clear geographical patterns within the results; studies performed in African countries often reported co-infection prevalence over 50% in TB cases [49,60,61,68]. As with measures of incidence, this wide variation in prevalence estimates may be in part due to the settings and characteristics of the prisoners themselves but also in part to methodological differences in calculation of prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…A recurring theme in the quest to improve treatment outcomes was loss to follow-up of patients released from prisons [61,74,89]. This topic has been the subject of numerous studies, particularly in regard to continuing HIV therapy [111,112].…”
Section: Discussionmentioning
confidence: 99%
“…Among 466 detainees beginning tuberculosis treatment at ten regional Ugandan prison health centres, only 222 (48%) completed treatment (202 [43%] were lost to follow-up and 22 [5%] died). 22 A chart review 75 of 202 detainees initiating tuberculosis treatment at one South African prison showed similar challenges: 92 (46%) patients were cured, but 103 (51%) had no ascertainable outcome because they were transferred before treatment completion. Findings that less than 50% of patients completed treatment or had documented cure are concerning, and have implications for the health of detainees and the potential development of drug-resistant tuberculosis.…”
Section: Tools Approaches and Structural Interventions To Preventiomentioning
confidence: 99%
“…These findings are similar to those of a study evaluating TB outcomes among prisoners in a correctional centre in North West Province South Africa. 27 Unemployment, which was another contributing factor to lack of cure, was similarly reported in the study done in Nigeria on the management outcome of pulmonary TB, and also in an Ethiopian study. 28,29 …”
Section: Discussionmentioning
confidence: 68%